Effects of Covid-19 on physical activity and eating behaviours and their mutual relationship - Munir, Fakhra; Ibrar, Rimsha; Malik, Yusra; Sana Bashir; Ashfaq, Madiha; Shafi, Hina (Journal of the Pakistan Medical Association, 2022)
The study aimed to determine the relationship between physical activity and eating behaviours among the physical therapy students of various physical therapy institutes of Rawalpindi/Islamabad during the Covid-19 pandemic. The study was conducted from September 2020 to February 2021. It was a cross sectional co-relational survey of a total of 209 physical therapy students, and the sampling technique was purposive sampling. Eating Attitude Test (EAT-26) Questionnaire and International Physical Activity Questionnaire (IPAQ) were used as the data collection tools. Healthy young students of 18-26 years of age, of both genders, were included and students with major functional limitations were excluded from the study. The results showed that 87 (41.6%) participants had normal EAT-26 scores whereas 122 (58.4%) had abnormal EAT-26 scores. —Continue